Ancient Jewish art and archaeology in the diaspora - Hachlili, Rachel. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1998)
Jewish Diaspora in Hellenistic, Roman and Byzantine periods from first to the eighth centuries C.E. is the subject of this work. The author thoroughly investigates origin, symbolism and significance of the mainly synagogal and funerary art forms in the Diaspora. Ancient Jewish Art and Archaeology in the Diaspora is the companion volume to the successful Ancient Jewish Art and Archeaeology in the Land of Israel (1988) by the same author. The geographical area covered includes Syria, Asia Minor, North Africa and Mediterranean Europe. The first section examines the characteristic features of Diaspora Art synagogue architecture and art (including the Torah shrine and mosaic pavements). Another section deals with burial and funerary practices. Of special importance are the sections on the Biblical scenes , designs and iconography of the Dura Europos synagogue, and the Jewish symbols such as the Menorah, ritual objects, the Ark, the conch and the Torah Scrolls . The book is richly illustrated with more than 325 drawings and photographs, some in colour.